Hubungan Asupan Cairan Ibu Hamil terhadap Indeks Cairan Amnion - Eny Fatmawati; Diah Rumekti Hadiati; Heru Pradjatmo (JURNAL KESEHATAN REPRODUKSI, 2018)
Introduction: Adequate amniotic fluid volume is a requirement for intra uterine fetal development and good pregnancy outputs / neonatal. Adequate intake of fluid in pregnant women can increase both the amniotic fluid index on oligohydramniotic or normoamniotic, but the scientific basis for the adequacy of the recommended daily fluid have not clear yet. Furthermore, the fluid intake counseling in addition to nutrition for pregnant women is neededObjective: To determine the fluid intake in pregnant women and the mean difference of  amniotic fluid index on adequate fluid intake compared to less fluid intake.Methods: This research used prospective observational cohort study, conducted against the third semester pregnant women in Puskesmas Mergangsan and Tegalrejo Yogyakarta during July until September 2014. The subjects who met the inclusion criteria were divided into adequate and less fluid intake groups. The correlation between fluid intake and amniotic fluid index was analyzed using t-test and linear regression.Result and Discussion: The total subjects who met the criteria were 27 people, consist of 12 people in adequate fluid intake group and 15 people in less fluid intake group. The mean of subject’s fluid intake 2078 ml (enough), while the mean of amniotic fluid index (AFI) 12,76 cm (normoamniotic).The result showed that there was a significant difference (3,50 cm (IK 95%; 1,5-5,48); P < 0,05) between the mean of AFI from adequate fluid intake group compared to less fluid intake group . Simple linear regression test showed the effect of fluid intake for AFI namely 31,7%; with the amount of predicted AFI = 10,686 + 3,545 x fluid intake – 1,015 x age – 1,317 x education + 0,314 x occupation (ARS= 44,5%). External variables (age, education, and occupation) had no significant effect for AFI .Conclusion : The mean preview of fluid intake in the third semester pregnant women in Yogyakarta was adequate. Moreover, there was a AFI signifficant difference between adequate fluid intake compared to less fluid intake.  Keywords: fluid intake; amniotic fluid index; AFI